PLAUR polymorphisms and lung function in UK smokers - Connolly Martin J; Wardlaw Andrew J; Moffat Miriam F; Parker Stuart G; Hall Ian P; Stewart Ceri E; Ruse Charlotte; Sayers Ian (BMC, 2009)
Abstract Background We have previously identified Urokinase Plasminogen Activator Receptor (PLAUR) as an asthma susceptibility gene. In the current study we tested the hypothesis that PLAUR single nucleotide polymorphisms (SNPs) determine baseline lung function and contribute to the development of Chronic Obstructive Pulmonary Disease (COPD) in smokers. Methods 25 PLAUR SNPs were genotyped in COPD subjects and individuals with smoking history (n = 992). Linear regression was used to determine the effects of polymorphism on baseline lung function (FEV1, FEV1/FVC) in all smokers. Genotype frequencies were compared in spirometry defined smoking controls (n = 176) versus COPD cases (n = 599) and COPD severity (GOLD stratification) using logistic regression. Results Five SNPs showed a significant association (p < 0.01) with baseline lung function; rs2302524(Lys220Arg) and rs2283628(intron 3) were associated with lower and higher FEV1 respectively. rs740587(-22346), rs11668247(-20040) and rs344779(-3666) in the 5'region were associated with increased FEV1/FVC ratio. rs740587 was also protective for COPD susceptibility and rs11668247 was protective for COPD severity although no allele dose relationship was apparent. Interestingly, several of these associations were driven by male smokers not females. Conclusion This study provides tentative evidence that the asthma associated gene PLAUR also influences baseline lung function in smokers. However the case-control analyses do not support the conclusion that PLAUR is a major COPD susceptibility gene in smokers. PLAUR is a key serine protease receptor involved in the generation of plasmin and has been implicated in airway remodelling.